Effects of The Addition of Carbon on Abaca Fiber and PVA Composite Materials Based on Mechanical and Acoustic Properties: Susilo Indrawati, Syabania R A, Linda Silvia, Lila Yuwana, Mochamad Zainuri - Susilo Indrawati Susilo Indrawati; Syabania R. A. Syabania R. A.; Linda Silvia Linda Silvia; Lila Yuwana Lila Yuwana; Mochamad Zainuri Mochamad Zainuri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2023)
Abaca is a kind of banana that grows in Indonesia. Abaca banana product utilized in this research is a fiber that obtained from the midrib of the stem. Henceforth, abaca fiber is processed to be the form of membranes. The purpose of the study are to determine the physical, mechanical and acoustic properties of abaca fiber composite materials as fillers and polyvinyl acetate (PVA) as a matrix. The ratio of composite materials of abaca fibers and PVA is 1:10. The variations used in producing membranes are the addition of carbon powders by 0%, 2%, 4%, 6% and 8%. The characteristics carried out include testing of density, morphology, tensile strength and sound absorption coefficient. The results reveal that the highest density is obtained from the sample of 0% carbon, i.e., 1.026 gr/cm3. Furthermore, the mechanical properties testing shows the highest yield stress value in samples with 4% carbon of 476.8 MPa and the highest Young modulus in samples with 8% carbon is 7905.1 MPa. Therefore, the addition of carbon could improve the mechanical properties of composites materials. Based on the measurement of sound absorption coefficient using an impedance tube with 1 microphone, the highest value can be attained from the sample of 4% carbon, namely 0.211 which shows the sample is more reflective. The material is reflective because the amount of abaca fiber used is less than PVA. The diameter of pores formed between the fiber and PVA are very small which could cause the absorption coefficient value to be lower. Therefore, further research will focus on the addition of abaca fiber content in composite materials. The positive point in this study is that the addition of carbon with 4% and 8% provides optimal mechanical ability.